MO690: Overview of Peritoneal Dialysis Outcomes in Northern Cyprus: A Nation-Based Study. (3rd May 2022) - Bardak, Simge; Behlul, Ahmet; Oygar, Deren
Abstract: BACKGROUND AND AIMS: Prevalence of patients with end stage renal disease (ESRD) undergoing renal replacement therapies (RRT) is increasing worldwide (Stel et al. Supplemented ERA-EDTA Registry data evaluated the frequency of dialysis, kidney transplantation, and comprehensive conservative management for patients with kidney failure in Europe.  Kidney Int. 2021;100 (1):182–95 and Bikbov et al.  Global, regional, and national burden of chronic kidney disease, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017. Lancet . 2020; 395 (10 225): 709–33). Epidemiology of ESRD and treatment options for these patients should be considered in health system planning (Bikbov et al.  Global, regional, and national burden of chronic kidney disease, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017. Lancet . 2020; 395 (10 225):709–33). By an enhanced national PD program, more patients may have chance to take advantage of this treatment option. In this study we aim to investigate whether PD is preferred as first dialysis treatment modality in Northern Cyprus and to evaluate PD duration, and outcomes in order to improve PD program. METHOD: PD patients aged above 18 years who were followed between 2003 and 2021 in Northern Cyprus were screened retrospectively. Demographic data, primary kidney diseases, comorbidities and previous RRT modalities were investigated. Episodes of peritonitis, transfer to automated PD in the follow-up, total duration on PD treatment, transfer to renal transplantation or HD and mortality rate were evaluated. Reasons for shifting from PD to HD were analysed. Outcomes of elderly (aged 65 years and above) and diabetic patients who were dropped out from PD were found out. RESULTS: A total of 123 patients (33 female/90 male) aged 18–83 years were included to the study. A total of 25 patients were actively doing PD, 2 moved to another country on PD therapy and 96 dropped out of PD. A total of 40% of 123 PD patients initiated RRT with PD (Fig. 1 ). Median time was found 1 month in the rest of patients to transfer PD from other modalities. Sixteen (16.8%) patients had renal transplantation during follow-up. Thirty-three patients (34.7%) transferred to HD. Insufficient dialysis (40.7%) and PD-related infections (29.6%) were the most common reasons for shifting from PD to HD (Fig. 2 ). Forty-six (48.4%) patients were died on PD therapy at the age of 67 ± 11. Cardiovascular events (50%) and various infections (35%) were the leading causes of mortality. A total of 48 (43.2%) PD patients had at least one episode of peritonitis. Automated PD was used by 58 (53.2%) patients. PD duration was 36 (1–150) months in patients who were dropped out of PD. Total duration on PD treatment was longer for males than females. Total duration on PD treatment, initiation RRT with PD, prevalence of hypertension, diabetes mellitus (DM), peritonitis and use of automated PD were not significantly different between elderly (patients aged ≥ 65 years, n  = 34) and younger individuals (18–65 years). Comorbidity index was found significantly higher in elderly group (P < 0.001). PD duration was longer for males then females ( P  = 0.044) and the duration was similar in patients with or without DM, in the dropped-out patients ( P  = 0.205). CONCLUSION: A significant amount of patients (60%) required HD before initiation of PD. Early admission of patients to nephrology department and timely initiation of education program may contribute to decrease need of HD before PD (Briggs et al . International variations in peritoneal dialysis utilization and implications for practice. Am J Kidney Dis.  2019; 74 (1): 101–10). As elderly patients had similar results with younger ones, age should not be considered as a challenging barrier for PD initiation. Precautions to prevent development of peritonitis, ultrafiltration failure and dialysis insufficiency may contribute to extent total duration on PD treatment.